Romantisme antara Norma dan Tradisi: Pembuatan Minuman Keras Tradisional Studi Kasus di Desa Wlahar Kecamatan Wangon - Ilham Mubarok, Dimas (Proceedings Series on Social Sciences & Humanities, 2024)
The aim of this study is to identify the power relationship between official norms and traditional alcoholic beverage production traditions at the community level. This case study was conducted in Wlahar village, Wangon district, where traditional wine production is still maintained. Although this practice is technically illegal, village communities preserve this tradition as a cultural heritage and livelihood. The research method used was qualitative ethnography and grounded theory using interviewing, observation, and document research techniques. Research shows that there is a relationship between strict official standards and local traditions that maintain traditional wine production. Village communities view this practice as a cultural identity and a source of economic income and thus seek to negotiate and restructure official norms in order to survive. Closer analysis shows that traditional wine making is a form of community culture that resists official legal regulations. On the other hand, countries should also consider cultural, social and economic aspects when developing guidelines for traditional alcoholic beverages. We hope that the results of this study can enrich discussions on the relationship between legal norms and local traditions in rural communities.